Furbish or perish: Italian social cooperatives at a crossroads. (January 2020) - Pansera, Mario; Rizzi, Francesco
Although the public debate tends to privilege investor-owned organisations, alternative forms of organisation are mushrooming at the borders of the capitalist economy. In this work, we contribute to the debate on alternative economies by analysing a specific form of worker-owned organisations which originated in Italy in the 1970s and was recognised by Italian legislation in the 1990s: the social cooperative. By drawing on data gathered over 3 years of participant observation, this article explores the tensions and contradictions generated by the rapid growth of an Italian social cooperative focused on waste recovery and its preparation for reuse. We show how social cooperatives might be able to reconcile their commercial success with their founding principles of equality and democratic management. This article contributes to the debate on the 'regeneration thesis' by providing new insights into the factors and drivers that force social cooperatives to scale up and to engage in competition with mainstream competitors, the internal conflicts and solutions that emerge in this process and the external alliances that social cooperatives can leverage to prosper and flourish.